1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 08:12:12
1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-
1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)
1、3.5X-14.5=3.X
2、0.2(3-X)=0.4(6-X)
1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)
3.5X-14.5=3X
3.5X-3X=14.5
0.5X=14.5
X=29
0.2(3-X)=0.4(6-X)
2(3-X)=4(6-X)
6-2X=24-4X
4X-2X=24-6
2X=18
X=9
1、移项0.5X=14.5
X=29
2、
先去括号再化简:
0.6-0.2X=2.4-0.4X
0.2X=1.8
X=9
1、3.5X-14.5=3.X2、0.2(3-X)=0.4(6-X)
7/x2+x+1/x2-x=6/x2-1
x2-3x+1=0 x2/(x4-x2+1)
x2-5x+1=0则x2+x2/1
x2-3x-1=0,求①x2 1/x2;②x2-1/x2
3.5x+1/2x2=30
y=x+√(1-x2) y2=x2+(1-x2)+2x√(1-x2)
解方程:X2--1/8(X2+2X)+X2+2X/3(X2--1)=11
解方程 2/(x2-x)+6/(1-x2)=7/(x2+x)x2为的平方
3/x2 -3x+2-1/x-2=1/x2 -x+4/x2 -2x
y=(x-1/X)(X2-1/X2)的导数,
x+1/x=3,求x2/x4+x2+1
2( x2 +1/x2) - 9( x + 1/x) + 14 =
解方程(x2+x+1)(x2+x+12)=42
因式分解(x2+x+1)(x2+x+2)-12=
解方程(x2+x)(x2+x-2)=-1
x2+x-6/(x2+x)+1=0怎么做
解方程x2-6/ x2-x=x-1